2013
DOI: 10.1016/j.jacc.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis and Systematic Review of the Predictive Value of Carotid Plaque Hemorrhage on Cerebrovascular Events by Magnetic Resonance Imaging

Abstract: Presence of IPH on MRI strongly predicts cerebrovascular events. Homogenization of future studies is warranted to allow for sufficient assessment of level of evidence for intervention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
192
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 276 publications
(200 citation statements)
references
References 34 publications
3
192
3
2
Order By: Relevance
“…Scanning time was 12 minutes 56 seconds. The T 1 turbo field echo sequence was acquired in sagittal orientation with a field of view of 200 × 250 × 200 mm 3 , an acquired voxel size of 1.0 × 1.0 × 0.5 mm 3 repetition time 4.8 ms, echo time 2.2 ms, flip angle 8°and scanning time was 1 minute 37 seconds.…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning time was 12 minutes 56 seconds. The T 1 turbo field echo sequence was acquired in sagittal orientation with a field of view of 200 × 250 × 200 mm 3 , an acquired voxel size of 1.0 × 1.0 × 0.5 mm 3 repetition time 4.8 ms, echo time 2.2 ms, flip angle 8°and scanning time was 1 minute 37 seconds.…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
“…1,2 Recent literature confirms that plaque characteristics may contribute to specify subgroups with an increased risk of (recurrent) ischemic cerebral events. [3][4][5] Moreover, the presence of infarcts in the brain parenchyma that downstream to these lesions may be important for accurate risk stratification. Patients with infarcts and cerebral symptoms were found to profit more from carotid endarterectomy (CEA), compared with patients with just ocular symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Carotid IPH has been shown to be a significant predictor of future cerebral infarction and stroke in patients with symptomatic carotid artery stenosis (3,4,12). A recent study by Hosseini et al (4) demonstrated that carotid IPH, measured as high signal intensity on MRI, predicted stroke in moderate degree stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the subgroup of 72 participants with 50% to 59% stenosis, IPH was significantly associated with future ipsilateral infarction and stroke. Saam et al (3) observed that the presence of IPH was associated with ~6-fold higher risk for cerebrovascular events. According to this study, the annualized event rate in subjects with detectable IPH was 17.71%, compared to 2.43% in patients without IPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation